National Asian American Survey (NAAS) Pre-Election Survey, (United States), 2016 - Ramakrishnan, S. Karthick (Subramanian Karthick) ([Verlag nicht ermittelbar], 2018)
The National Asian American Survey (NAAS) Pre-Election Survey, 2016 contains nationally representative data from telephone interviews of adult U.S. residents who self-identified as Asian/Asian American, Native Hawaiian or Pacific Islander, White, African American/Black, Hispanic/Latino, and Multiracial. The survey included sizable samples of Asian Americans in 9 Asian national origin groups (Chinese, Filipino, Indian, Vietnamese, Korean, Japanese, Hmong, Cambodian), as well as Native Hawaiian/Pacific Islanders. The survey instrument included questions about immigrant background, social identities, social attitudes, political behavior, and policy attitudes. Demographic information included age, race, language, gender, country of birth, religion, marital status, educational level, employment status, citizenship status, household income, and size of household. The study contains 1 data file (316 variables, 4787 cases).